2007
DOI: 10.1093/brief-treatment/mhm018
|View full text |Cite
|
Sign up to set email alerts
|

In Whose Best Interest? A Canadian Case Study of the Impact of Child Welfare Policies in Cases of Domestic Violence

Abstract: Always cite the published version, so the author(s) will receive recognition through services that track citation counts, e.g. Scopus. If you need to cite the page number of the author manuscript from TSpace because you cannot access the published version, then cite the TSpace version in addition to the published version using the permanent URI (handle) found on the record page.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Practices that draw upon a deficit model of mothering are likely to be experienced by women as punitive, particularly if they are not followed by more positive practical and emotional support strategies. They are also likely to discourage abused women from reaching out for assistance (DeVoe & Smith 2003; Peckover 2003; Alaggia et al. 2007).…”
Section: Implications Of a Deficit Model Of Mothering For Child Welfamentioning
confidence: 99%
See 1 more Smart Citation
“…Practices that draw upon a deficit model of mothering are likely to be experienced by women as punitive, particularly if they are not followed by more positive practical and emotional support strategies. They are also likely to discourage abused women from reaching out for assistance (DeVoe & Smith 2003; Peckover 2003; Alaggia et al. 2007).…”
Section: Implications Of a Deficit Model Of Mothering For Child Welfamentioning
confidence: 99%
“…Moreover, few women reported that they had been able to identify service providers with appropriate expertise to support them and their children. Research also shows that women who are marginalized on the basis of class, sexual orientation, race, immigration status and ability may face greater barriers in seeking help and accessing services for themselves and for their children (Alaggia et al. 2007).…”
Section: Implications Of a Deficit Model Of Mothering For Child Welfamentioning
confidence: 99%
“…Negative experiences were far more common for these women and reflected the convoluted bureaucratic system and ineffectual services that made it challenging for them to access effective support within the criminal justice system, as well as negative attitudes and ineffective systems that left them feeling revictimized. These findings further highlight the challenges of the justice system to effectively support survivors of domestic violence who report their abuse (Cerulli et al 2011;Gillis et al 2006;Lutenbacher et al 2003), as well as the reluctance of abused women to disclose or seek services for their families (Alaggia, et al 2007). …”
Section: Discussionmentioning
confidence: 80%
“…Qualitative interviews with mothers who are CPS clients in Canada and the United States demonstrate that the interviewees believe that social workers made them accountable for IPV, as the workers pressured them to leave their abusive partners but did not offer any concrete assistance or resources that would allow them to leave safely (Alaggia et al, 2007;Johnson and Sullivan, 2008;Shim and Haight, 2006). A recent study from Ireland documents similar findings as women reported that CPS workers failed to understand the dynamics of IPV and expected them to be able to easily leave their partners and homes; they, too, reported that they did not receive help in making these changes (Buckley et al, 2011).…”
Section: Recognition and Intervention In Situations Involving Intimatmentioning
confidence: 99%